The standards [compact disc] - Estefan, Gloria (Sony Music Latin, 2013)
Gloria Estefan puts her own unique spin classic songs from the Great American Songbook. Along with adding new touches, she collaborates with such artists as Laura Pausini, Dave Koz, and Joshua Bell.